Companion to Satire. - Quintero, Ruben (John Wiley & Sons, 2007)
This collection of twenty-nine original essays, surveys satire from its emergence in Western literature to the present. Tracks satire from its first appearances in the prophetic books of the Old Testament through the Renaissance and the English tradition in satire to Michael Moore's satirical movie Fahrenheit 9/11. Highlights the important influence of the Bible in the literary and cultural development of Western satire. Focused mainly on major classical and European influences on and works of English satire, but also explores the complex and fertile cultural cross-semination within the tradit.